Linguistic Peculiarities of G. Bush’s and B. Obama’s Speeches on the Armenian Genocide - Tchaparian, Vicky (Armenian Folia Anglistika, 2015)
The present article aims to reveal the peculiarities of the language units chosen and stringed together in the speeches on the Armenian Genocide made by George Bush and Barak Obama before and after their presidency. An attempt is made to reveal the functional and linguostylistic peculiarities that condition the ideological aspect of George Bush’s and Barack Obama’s speeches. Words, word combinations, syntagms that are part of the whole linguistic system are studied as means of realization of a certain ideological function.
Keywords: George Bush; Barak Obama; transformation of ideology; the Armenian American community mislead; policy of Realpolitik vs. morality